HINT1 aggravates aortic aneurysm by targeting ITGA6/FAK axis in vascular smooth muscle cells - Zhang, Yan; Wu, Wencheng; Yang, Xuehui; Luo, Shanshan; Wang, Xiaoqian; Da, Qiang; Yan, Ke; Hu, Lulu; Sun, Shixiu; Du, Xiaolong; Li, Xiaoqiang; Han, Zhijian; et al. (The Journal of Clinical Investigation, 2025)
Aortic aneurysm is a high-risk cardiovascular disease without an effective cure. Vascular smooth muscle cell (VSMC) phenotypic switching is a key step in the pathogenesis of aortic aneurysm. Here, we revealed the role of histidine triad nucleotide-binding protein 1 (HINT1) in aortic aneurysm. HINT1 was upregulated both in aortic tissue from patients with aortic aneurysm and angiotensin II–induced aortic aneurysm mice. VSMC-specific HINT1 deletion alleviated aortic aneurysm via preventing VSMC phenotypic switching. With the stimulation of pathological factors, the increased nuclear translocation of HINT1 mediated by nucleoporin 98 promoted the interaction between HINT1 and transcription factor AP-2 α (TFAP2A), further triggered the transcription of integrin α6 (ITGA6) mediated by TFAP2A, and consequently activated the downstream focal adhesion kinase (FAK)/STAT3 signal pathway, leading to aggravation of VSMC phenotypic switching and aortic aneurysm. Importantly, defactinib treatment was demonstrated to limit aortic aneurysm development by inhibiting the FAK signal pathway. Thus, the HINT1/ITGA6/FAK axis emerges as a potential therapeutic strategy in aortic aneurysm.